The Relationship Between Social Comparison and Body Dissatisfaction on Students at Muhammadiyah University of Sidoarjo: Hubungan Antara Perbandingan Sosial dengan Ketidakpuasan Tubuh pada Mahasiswi di Universitas Muhammadiyah Sidoarjo - Permatasari, Novita Gusti; Ansyah, Eko Hardi (Universitas Muhammadiyah Sidoarjo, 2023)
This study aims to determine the relationship between social comparison and body dissatisfaction among female students at Muhammadiyah University of Sidoarjo. This study uses a correlational quantitative approach. The hypothesis in this study is that there is a relationship between social comparison and body dissatisfaction among female students at Muhammadiyah University of Sidoarjo. The sampling technique in this study used Quota Sampling with a sample of 362 female students from a total population of 6,104. The measuring instrument used for data collection uses a social comparison scale adapted from Hastuti (2018) research with a reliability level of 0.821, and a body dissatisfaction scale adapted using research from Kumalasari (2015) with a reliability level of 0.807. The data collection technique used a questionnaire via google form and distributed directly and the data analysis in this study used the Person Product Moment correlation test with the help of the SPSS 21 statistical application for windows, the results were (r) = 0.380; significance of 0.000 (p<0.05). The results of this study indicate that there is a positive relationship between social comparison and body dissatisfaction among female students at Muhammadiyah University of Sidoarjo. So that the hypothesis proposed in this study is accepted, it means that the higher the social comparison among female students, the higher the body dissatisfaction among female students. And conversely, the lower the social comparison among female students, the lower the body dissatisfaction among female students. The effective contribution of the body dissatisfaction variable is 14.4% to social comparison.